Pengaruh Kemampuan dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Badan Kesatuan Bangsa dan Politik (BAKESBANGPOL) Kabupaten Probolinggo - Fida Dian Nofita; Ngatimun Ngatimun; Dedi Joko Hermawan (Fakultas Ekonomi Universitas Panca Marga, 2017)
The purpose of this study is 1) To determine the effect between the variable ability and organizational commitment simultaneously on the performance of employees at the Unity, Nation, and Politics (Bakesbangpol) Probolinggo. 2) To know the influence between the variable ability and organizational commitment partially on the performance of employees at the Unity, Nation, and Politics (Bakesbangpol) Probolinggo. 3) To know the dominant variable between organizational capability and commitment to employee performance at Badan Unity, Bangsa dan Politik (Bakesbangpol) Probolinggo District. Researcher uses descriptive with the approach of causal associative and takes sample counted 31 respondents, method of collecting data using questioner and sampling technique using saturated sampling. The analysis tool used is a questionnaire test consisting of validity test and reliability test, classical assumption test, multiple regression test, hypothesis test consisting of t-test, F test, and the dominant test. The result of the validity test shows all the valid question items above 0.367 and the result of the reliability test shows the reliable result that is above 0.60. Normality test shows normally distributed data. Multicollinearity test shows the independent variable (X) and the dependent variable (Y) there is no correlation between independent variables or free regression model of multicollinearity. Heteroscedasticity test showed no heteroscedasticity. Autocorrelation test showed no autocorrelation occurred. F test shows that the independent variables simultaneously affect the purchase decision (Y) with the value Fcount> Ftable (36.637> 3.34) (sig. 0.000 <0.05). The t-test shows that the variable of the ability variable (X1) has a partial effect on the performance (Y) with the tcount> table (6,175> 2.048) (sig .0,00,05). And the commitment variable (X2) has a partial effect on the performance (Y) with the value of count (5.427 ≥ 2.048) (sig. 0.000 ≤ 0,05). This study supports the results of research conducted by Sitorus (2014), Permatasari (2016), and Shafiah (2014). Keywords: Ability, Organizational Commitment, and Performance.